An integrated service architecture for managing capital market systems. - Rabhi, F.A.
This article studies current developments and trends in the area of capital market systems. In particular, it defines the trading lifecycle and the activities associated with it. The article then investigates opportunities for the integration of legacy systems and existing communication protocols through distributed integrated services that correspond to established business processes. These integrated services link to basic services such as an exchange, a settlement, or a registry service. Examples of such integrated services include pre-trade services (e.g., analytics) or post-trade services (e.g., surveillance). The article then presents the various levels of integration in capital market systems and discusses the standards in place. It establishes that most interactions occur at a low level of abstraction such as the network (e.g., TCP/IP), data format (e.g., FIX, XML), and middleware levels (e.g., CORBA). Finally, the article discusses a software development methodology based on the use of design patterns. These design patterns address the essential aspects of managing integrated services in a technology-independent fashion. These aspects are service wrapping, service composition, service contracting, service discovery, and service execution. The objective of the methodology is to facilitate the rapid development of new integrated services that correspond to emerging business opportunities
Keywords: CORBA; FIX; Internet; TCP/IP.; Web; XML; Business processes; Capital market systems management; Communication protocols; Data format; Design patterns; Distributed integrated services; Exchange; Integrated service architecture; Legacy systems; Middleware; Post-trade services; Pre-trade services; Registry service; Service composition; Service contracting; Service discovery; Service execution; Service wrapping; Settlement; Software architecture; Software development; Standards; Surveillance; Trading lifecycle